The Effectiveness of Fly Ash as a Substitute of Cement For Marine Concrete - Naibaho, Armin (Civil Engineering Journal, 2018)
The purpose of this research is to know the effectiveness of fly ash waste in marine concrete related to the average compressive strength to be used as a substitute for cement. The test is done for concrete base material, namely: coarse aggregate (gravel), fine aggregate (sand), fly ash, cement (PC = Portland Cement), water and additional material (superplasticizer). 10 cylinders were given each treatment with (0 %, 10 %, 20 %, 25 %) percentage of fly ash addition. The samples then soaked for 26 days in seawater. At 28th day, the sample was subjected to a compression test. Based on the results of analysis and discussion, then obtained: (1) The use of 10% fly ash amount will produce the biggest compressive strength Â =Â  65.84 MPa; (2) When compared with the average compressive strength, the sample without using fly ash (0 %) has compressive power 62.02 MPa and 6.16 % increase in average compressive strength on the addition of 10 % fly ash 65.84 MPa, but in addition to 20 % fly ash there was a decrease of 9.13 % (56.36 MPa) and in addition of 25 % fly ash the average compressive strength decrease to 22.49 % (48.07 MPa).